On a Subclass of Analytic and Univalent Functions with Positive Coefficients Defined by a Differential Operator - Al-khafaji, Aqeel Ketab (Iraqi Journal of Science, 2021)
In this paper, a differential operator is used to generate a subclass of analytic and univalent functions with positive coefficients. The studied class of the functions includes: which is defined in the open unit disk satisfying the following conditionThis leads to the study of properties such as coefficient bounds, Hadamard product, radius of close –to- convexity, inclusive properties, and (n, τ) –neighborhoods for functions belonging to our class.